A multifactorial histopathologic score for the prediction of prognosis of resected esophageal adenocarcinomas after neoadjuvant chemotherapy - Langer, Rupert; Peters, Leila; Büchler, Markus W.; Weichert, Wilko; Ott, Katja (Annals of surgical oncology, 2014)
For esophageal adenocarcinoma treated with neoadjuvant chemotherapy, postoperative staging classifications initially developed for non-pretreated tumors may not accurately predict prognosis. We tested whether a multifactorial TNM-based histopathologic prognostic score (PRSC), which additionally applies to tumor regression, may improve estimation of prognosis compared with the current Union for International Cancer Control/American Joint Committee on Cancer (UICC) staging system.
Published: 27 November 2013
Gesehen am 12.08.2020